Disequilibrium of M1 and M2 Macrophages Correlates with the Development of Experimental Inflammatory Bowel Diseases. (October 2014) - Zhu, Wei; Yu, Jianbo; Nie, Ying; Shi, XueKui; Liu, Yang; Li, Fujuan; Zhang, Xiao-li
<x xml:space="preserve">Abstract</x> Ulcerative colitis, a major inflammatory bowel disease, is an idiopathic inflammatory disorder of the colonic mucosa, accompanied by an aberrant immune reaction to intestinal microflora. Macrophages are central mediators of intestinal immune homeostasis and inflammation. The relationship between macrophages and the pathogenesis of colitis is poorly understood. We aimed to characterize the changing populations and roles of M1/M2 macrophages in colitis. We demonstrated that M1 macrophages increased and M2 macrophages decreased in colitis, accompanied by Interleukin (IL)-23 and Tumor necrosis factor-α induction and IL-10 suppression. Transfer of M2 macrophages reduced dextran sodium sulfate-induced colitis by inducing IL-10 production and promoting regulatory T-cell generation. In vivo neutralization of IL-10 partially reduced the effects of M2 transfer. These findings suggest that macrophages play a critical role in colitis; specifically, disequilibrium of macrophage subsets promotes colitis development. A shift from the M1 to M2 phenotype reduces colitis by inducing IL-10; thus, mobilization of M2 macrophages could be a novel approach to colitis therapy.